Virtual Prototyping for Construction Site Co2 Emissions and Hazard Detection. (22nd August 2014) - Wong, Johnny Kwok Wai; Li, Heng; Chan, Greg; Wang, Haoran; Huang, Ting; Luo, Eric; Li, Vera
The need for an efficient means of managing emissions and identifying potential hazard black spots in construction processes effectively and at the lowest cost possible has been highlighted in the construction sector. This study illustrates an integrated 5D model developed for quantifying carbon emissions and simulating the pattern of emissions of construction processes as a whole using virtual prototyping technologies. The predicted construction emissions data for each activity is generated and plotted to visually demonstrate the emission rates alongside the integrated four-dimensional VP framework of the construction project. The model also consists of a pro-active construction management system (PCMS), which assist the project team to detect sources of danger to on-site workers and provide pro-active warnings to them so as to avoid fatal accidents that are often caused by falling from heights and being struck by moving objects. A Hong Kong high-rise housing development project is used to exhibit the application of the carbon emission visualisation and potential accident detection system. This tool aims to encourage construction industry practitioners to become more environmentally conscious and pro-active in carbon mitigation and safety performance.